Phosphatidic acid as a second messenger in human polymorphonuclear leukocytes. Effects on activation of NADPH oxidase. - Agwu, D E (1991)
Receptor-mediated agonists, such as FMLP, induce an early, phospholipase D (PLD)-mediated accumulation of phosphatidic acid (PA) which may play a role in the activation of NADPH oxidase in human PMN. We have determined the effect of changes in PA production on O2 consumption in intact PMN and the level of NADPH oxidase activity measured in a cell-free assay. Pretreatment of cells with various concentrations of propranolol enhanced (less than or equal to 200 microM) or inhibited (greater than 300 microM) PLD-induced production of PA (mass and radiolabel) in a manner that correlated with enhancement or inhibition of O2 consumption in PMN stimulated with 1 microM FMLP in the absence of cytochalasin B. The concentration-dependent effects of propranolol on FMLP-induced NADPH oxidase activation was confirmed by direct assay of the enzyme in subcellular fractions. In PA extracted from cells pretreated with 200 microM propranolol before stimulation with 1 microM FMLP, phospholipase A1 (PLA1)-digestion for 90 min, followed by quantitation of residual PA, showed that a minimum of 44% of PA in control (undigested) sample was diacyl-PA; alkylacyl-PA remained undigested by PLA1. Propranolol was also observed to have a concentration-dependent enhancement of mass of 1,2-DG formed in PMN stimulated with FMLP. DG levels reached a maximum at 300 microM propranolol and remained unchanged up to 500 microM propranolol. However, in contrast to PA levels, the level of DG produced did not correlate with NADPH oxidase activation. Exogenously added didecanoyl-PA activated NADPH oxidase in a concentration-dependent manner (1-300 microM) in a reconstitution assay using membrane and cytosolic fractions from unstimulated PMN. In addition, PA synergized with SDS for oxidase activation. Taken together, these results indicate that PA plays a second messenger role in the activation of NADPH oxidase in human PMN and that regulation of phospholipase D is a key step in the activation pathway.